2013
DOI: 10.5539/jfr.v2n3p46
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Social Support System for Improving Food Security Among the Elderly Headed Household in Communal Areas of Zimbabwe

Abstract: The study sought to establish factors that contribute towards food security among elderly headed households and then seek ways of enhancing them. The study was conducted in Mudzi District in Mashonaland East Province of Zimbabwe. Data was collected from wards 11, 12 and 16. The study used cross sectional household data collected using a structured questionnaire. Two measures of food security are used; namely household food insecurity access score and household dietary diversity score. The results showed that f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Participation in groups and social networks generally has reduced household vulnerability (Dershem and Gzirishvili, 1998). In particular, social networks have a positive influence on desirable health indicators (Brune and Bossert, 2009;Adelman, 2013), strengthen property rights by encouraging social reciprocity that facilitates collective action against coercive undertakings, and enhance food security status (Nyikahadon et al, 2013). In rural African communities, the support of social networks (extended family, friends, and neighbours) is essential in borrowing or leveraging land, labour, food, and money, especially at times of social and financial turmoil (Kebede and Butterfield, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Participation in groups and social networks generally has reduced household vulnerability (Dershem and Gzirishvili, 1998). In particular, social networks have a positive influence on desirable health indicators (Brune and Bossert, 2009;Adelman, 2013), strengthen property rights by encouraging social reciprocity that facilitates collective action against coercive undertakings, and enhance food security status (Nyikahadon et al, 2013). In rural African communities, the support of social networks (extended family, friends, and neighbours) is essential in borrowing or leveraging land, labour, food, and money, especially at times of social and financial turmoil (Kebede and Butterfield, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in developing a link between DEWS and food security, the survey questionnaire contained a component of dietary diversity assessment [29]. Dietary diversity is a qualitative measure of food consumption reflecting the households' access to a variety of foods.…”
Section: Data Collectionmentioning
confidence: 99%
“…Respondents were asked to score on the food items they consumed in the last 24 h. The food items included cereals, vitamin-rich vegetables, roots and tubers, dark leafy vegetables, other vegetables; vitamin A fruits; other fruits; meat, poultry, offal; eggs; fish; pulses/groundnuts/legumes; milk and milk products; oil/fats; sugar/honey. The expected response was either yes = 1 or no = 0 following Kefasi Nyikahadzoi [29] method.…”
Section: Data Collectionmentioning
confidence: 99%
“…Instrumental social support, referring to practical help that serves a particular function such as cash loans or labour in-kind, is thought to most effectively foster improved food security in comparison to emotional, informational, or companionship social support (Cohen and Wills 1985; Tsai et al 2011). Relatively few previous studies in sub-Saharan Africa have examined the relationship between food insecurity and social support (Hadley, Mulder, and Fitzherbert 2007; Frongillo, Valois, and Wolfe 2003; Nyikahadzoi et al 2013; Lemke et al 2003). A mixed-methods study in South Africa found that female-headed households had better nutrition security than male-headed households, which was attributed to women's reliance on and fostering of social ties and networks (Lemke et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…A mixed-methods study in South Africa found that female-headed households had better nutrition security than male-headed households, which was attributed to women's reliance on and fostering of social ties and networks (Lemke et al 2003). A cross-sectional study in Zimbabwe found that elderly-headed households had greater food security compared to households headed by younger people, and social capital increased the elderly headed household's likelihood of being food secure (Nyikahadzoi et al 2013). One study in rural Tanzania demonstrated that measures of wealth and social support were strongly associated with greater food security (Hadley, Mulder, and Fitzherbert 2007).…”
Section: Introductionmentioning
confidence: 99%